Establishing an injury surveillance system in German youth elite snowboarding - Eberhardt, A.; Wulff, J.; Frohberg, F. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The risk of injury in snowboarding (SNB) is high, whereas the incidence and type of injury differ depending on discipline and performance level. In SNB Cross, Big air and Halfpipe disciplines occur a higher amount of contact injuries and (landing) falls than in SNB Slalom disciplines. While wrist injuries dominate in the recreational athletes, knee and back injuries are dominant among elite athletes. The lower the rider`s skill level, the higher the risk of injury, but the severity of injuries (multiple injuries involving the trunk) increases with skill level. So far, there are no standardized raised epidemiological injury data for junior elite SNB. Therefore, it is not clear how these correlations operate in young athletes regarding their non-linear growth and maturation phases involving unequal developing state of skeletal, muscular and nervous system. Injury surveillance in junior athletes is particularly difficult. There is no central point of contact where data can be collected regularly in a standardized and comprehensive manner. Further, medical care in junior elite sport is usually organized decentralized by individual physicians or institutions. Therefore, thegoal was to establish a coach-centered and largely automated system of injury surveillance at national level that fits the general conditions in German junior snowboarding.